Hiszpańskie i niemieckie osiągnięcia w rozwoju energetyki odnawialnej: aspekt prawny - Leszek Karski (Studia Ecologiae et Bioethicae, 2004)
Certainly, the renewable energy sector in Poland should be the beneficiary of the European Union enlargement. It results from both the energy policy and EU law. Poland should adopt national law to the EU requirements in the field of renewable energy sources. Polish legislators may rest on other countries' experiences in this subject. We especially should take into consideration Spanish and German measures. Spanish and German mechanisms of support for renewable energy sources at the national level are very interesting solutions. Those measures are intended to help to attain objectives such as meeting the commitments given on climate change, environmentally sustainable security of supply, and promotion of renewable energy sources. The article is an analysis of Spanish and German support systems in view of the modification of Polish law in the field of renewable energy sources.